ZCF32, a fungus specific Zn(II)2 Cys6 transcription factor, is a repressor of the biofilm development in the human pathogen Candida albicans - Kakade, Pallavi (Sci Rep, 2016)
As a human fungal pathogen, Candida albicans can cause a wide variety of disease conditions ranging from superficial to systemic infections. Many of these infections are caused by an inherent ability of the pathogen to form biofilms on medical devices resulting in high mortality. Biofilms formed by C. albicans are a complex consortium of yeast and hyphal cells embedded in an extracellular matrix and are regulated by a network of transcription factors. Here, we report the role of a novel Zn(II)2-Cys6 binuclear cluster transcription factor, ZCF32, in the regulation of biofilm formation. Global transcriptome analysis reveals that biofilm development is the most altered pathway in the zcf32 null mutant. To delineate the functional correlation between ZCF32 and biofilm development, we determined the set of genes directly regulated by Zcf32. Our data suggests that Zcf32 regulates biofilm formation by repressing the expression of adhesins, chitinases and a significant number of other GPI-anchored proteins. We establish that there is the lesser recruitment of Zcf32 on the promoters of biofilm genes in biofilm condition compared to the planktonic mode of growth. Taking together, we propose that the transcription factor ZCF32 negatively regulates biofilm development in C. albicans.